Clear cell mammary malignant myoepithelioma with abundant glycogens. Issue 8 (August 1997) - Kuwabara, H; Uda, H
Abstract : Malignant myoepithelioma (myoepithelial carcinoma) of the breast is extremely rare. A case is reported of a 46 year old female with clear cell mammary malignant myoepithelioma that, on histological examination, was glycogen abundant clear cell carcinoma. Immunohistochemically, the clear cells showed myoepithelial differentiation–that is, they were a smooth muscle actin and S100 protein positive. This case shows that glycogen abundant clear cell carcinoma is a variant of malignant myoepithelioma of the breast.